1999
DOI: 10.1007/s004210050548
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective ? blockade attenuates the recruitment of CD62L? T lymphocytes following exercise

Abstract: Exercise induces a selective redistribution of CD62L(-) T lymphocytes. This study examined the effects of beta adrenergic receptor blockade on this phenomenon. Twelve healthy men were exercised to exhaustion on a treadmill prior to and following 1 week of treatment with the nonselective beta antagonist propranolol or the beta1 selective antagonist metoprolol. Dynamic exercise resulted in a significant lymphocytosis (p < 0.001). CD8(+)CD62L(-) T cells showed a greater than 3-fold increase in response to exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 8 publications
(22 reference statements)
4
14
0
1
Order By: Relevance
“…The epinephrine-induced mobilization of effector CD8 + T cells is consistent with previous studies of increased effector CCR7 2 / CD62L 2 CD45RA + CD8 + T cell numbers after stress or catecholamine administration (19,22,25). These effector CD8 + T cells represent a stage of T cell differentiation occurring late in the immune response, and are hence called terminally differentiated cytotoxic T cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The epinephrine-induced mobilization of effector CD8 + T cells is consistent with previous studies of increased effector CCR7 2 / CD62L 2 CD45RA + CD8 + T cell numbers after stress or catecholamine administration (19,22,25). These effector CD8 + T cells represent a stage of T cell differentiation occurring late in the immune response, and are hence called terminally differentiated cytotoxic T cells.…”
Section: Discussionsupporting
confidence: 90%
“…We show that stresslike increases in epinephrine concentrations invoke a specific increase in immune subpopulations with cytotoxic effector potential, namely, effector CD8 + T cells It has been repeatedly demonstrated that the number of immune cells increases after physical exercise or mental stress, with the most pronounced increases occurring in NK cell and CD8 + cytotoxic T cell counts (3,5,16,34), whereas both populations are decreased when endogenous catecholamines are suppressed by stellate ganglion block (40). These effects are caused by adrenal medullary epinephrine binding to b2-adrenoceptors on PBMCs, with high and intermediate levels of b2-adrenoceptor expression on NK cells and cytotoxic T cells, respectively (1,3,7,8,19,33,41). Our findings substantially expand these previous findings in showing that the epinephrine-induced increase in circulating immune cells is highly specific to cytotoxic effector subtypes, namely, effector CD8 + T cells, g/d T cells, NKT-like cells, cytotoxic NK cells, and proinflammatory monocytes, whereas no change is seen for cells lacking any cytotoxic potential, namely, CD4 + T cells, CD8 + T cells at their early stage of differentiation, immunomodulatory NK cells, and conventional monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described (Mills et al 1999), ow cytometry using CellQuest software (FACSCalibur, Becton Dickinson, San Jose, Calif.) was used to quantify leukocytes and lymphocyte subsets and CD62L and CD54 expression. A complete blood count (CBC) analysis was performed by using a Coulter STKS CBC Counter.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Os efeitos deste tipo de exercício físico sobre o aumento no número de leucócitos circulantes são mediados, pelo menos em parte, pela ativação do sistema nervoso simpático 29 e aumento agudo dos níveis séricos de catecolaminas durante o exercício 30 .…”
Section: Discussionunclassified